The Influence of Work Discipline and Work Motivation on Employee Performance - Syaefulloh, Asep (Greenation International Journal of Tourism and Management, 2025)
The purpose of this research is to determine and analyze: (1) Work Motivation (2) Work Discipline; (3) Performance; and (4) the Influence of Work Motivation and Work Discipline on Employee Performance at Pharmacy School X in Bandung City, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at the X School of Pharmacy in Bandung City, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Work Motivation of Employees at Pharmacy School X in Bandung City is mostly rated quite well by the Employees; the work discipline of Employees at Pharmacy School X in Bandung City can generally be considered good, and the Performance of Employees at Pharmacy School X in Bandung City is currently rated as good. Work motivation and work discipline simultaneously affect employee performance at Pharmacy School X in Bandung City. However, partially, Work Motivation has a more dominant influence on Employee Performance than Work Discipline. Because Work Motivation more dominantly influences performance, it becomes the top priority in improving Employee performance. therefore, the X Pharmacy School in Bandung City is expected to improve Employee Work Motivation at the X Pharmacy School in Bandung City by involving them in training and education, so that they can work more professionally.